Governan??a corporativa e gerenciamento de projetos: um estudo de caso sobre as bases do processo decis??rio em projetos - Ferrer, Paulo Sergio Scoleze (2016)
The emergence of large corporations, geographically dispersed and wide range of business, brought new challenges to its managers and owners. The impossibility to exert a direct and continuous supervision over all decision-making processes occurring in each portion or unit that makes up the organization, resulted in developing the concept of corporate governance, which aims to place beacons to the decisions of the various agents, opposing business risks to the policies that attempt to protect the interests of the owners or investors. Due to its characteristics, to projects are inherent risks and uncertainties, indicating the relevance of the integration of project governance to the organization's governance model. However, an examination of the literature reveals some incipiency in studies of this relationship, which tend to extol the project performance metrics at the expense of the paths leading to their results. From this gap, emerges as objective of this work, the analysis of interconnection between the decision-making process on projects and corporate governance. When highlighting the morphology of decision making in project management through a multiple case study, the results of this research suggests the underdevelopment of corporate governance mechanisms, apparently not robust enough to permeate the organization and reach the decision maker agent in the project. However, when isolated initiatives break the gap between temporary organization (project) and the permanent organization, decisions aligned with the guidelines of corporate governance are now 10.4 times more frequent, suggesting a significant influence. In practice, this finding hints the possibility of organizations being exposed to unknown and possibly significant risks, encouraging the discussion about the real efficiency of corporate governance mechanisms, by a perspective of permeability through the projects encompassed by the corporation.